Meta-analysis of the Clinical Efficacy and Safety of High- and Low-dose Methylprednisolone in the Treatment of Children With Severe Mycoplasma Pneumoniae Pneumonia. Issue 3 (March 2020) - Sun, Lin-Li; Ye, Chao; Zhou, Yu-Lu; Zuo, Shan-Ru; Deng, Zhen-Zhen; Wang, Chun-Jiang
Abstract : Background: Mycoplasma pneumoniae pneumonia is generally a self-limiting disease, but it can develop into severe Mycoplasma pneumoniae pneumonia (SMPP). Immunologic mechanisms are thought to play an important role in the pathogenesis of SMPP. Therefore, the use of systemic glucocorticoids may have beneficial effects. However, to date, the use of glucocorticoid therapy in SMPP is limited to small case series, and the glucocorticoid dosage for children with SMPP has not been established. Methods: Here, we used a meta-analysis method to collect data from randomized control trials of different doses of methylprednisolone in SMPP to assess the safety and efficacy of treatment with low- versus high-dose methylprednisolone in children with SMPP. Results: We included 13 Chinese randomized control trials that included 1049 children. The high- and low-dose groups were comprised of 524 and 525 children, respectively. The high-dose group was significantly more effective than the low-dose group in clinical efficacy [risk ratio = 1.30, 95% confidence interval (CI) (1.23, 1.38), P < 0.05]. In addition, compared with low-dose methylprednisolone, high-dose methylprednisolone significantly shortened hospital stays and antipyretic therapy, pulmonary rales disappearance, cough disappearance and pulmonary shadow absorption times. There was no significant difference in adverse events between the high- and low-dose groups: risk ratio= 0.85, 95% CI (0.53, 1.36), P > 0.05. Conclusions: We conclude that high-dose methylprednisolone is effective in the treatment of SMPP without increasing the incidence of adverse reactions. Abstract : Supplemental Digital Content is available in the text.